Analysis of JAK2 V617F mutation in Tunisian patients with myeloproliferative neoplasms. (April 2021) - Chadi, Soumaya; Dhaouadi, Tarak; Sfar, Imen; Baccouche, Hela; Nabli, Rym; Ben Romdhane, Neila; Ben Abdallah, Taïeb; Gorgi, Yousr
We aimed to investigate the prevalence of the JAK2 V617F mutation in Tunisian patients with myeloproliferative neoplasms (MPN) and to look for possible associations with diseases' presentation. In this context, JAK2 V617F polymorphism was detected by PCR-RFLP and direct sequencing in 213 MPN patients (109 with polycythemia vera (PV), 93 with essential thrombocythemia (ET) and 11 with primary myelofibrosis (PMF)), 77 unclassified patients with thrombosis (UPT) and 95 healthy control subjects. The JAK2 V617F mutant allele was present by either PCR-RFLP or direct sequencing in 158 (74.17%) MPN patients while all UPT and controls were negative. Besides, the JAK2 V617F mutation was significantly more frequent in patients with PV 98 (89.9%) than in ET 54 (58.1%) and PMF 6 (54.5%) groups, p < 0.001. Analytic results in MPN patients showed significant associations between the JAK2 SNP and both hemoglobin levels (16.29 ± 3 vs 13.01 ± 3.65) and hematocrit (52.99 ± 8.34 vs 45.37 ± 10.94), p < 0.001 and p < 0.001, respectively. In addition, in the ET subgroup thrombosis was significantly more frequent in patients carrying the V617F mutation (16, (29.6%) vs 3, (7.7%)), p = 0.01. In ET patients, the V617F mutation seems to be predictive of thrombosis occurrence.